Advertising and Heritage Interpretation - Nechita, Florin; Csesznek, Codrina; Candrea, Adina Nicoleta; Țăranu, Dan (My University, 2014)
This book documents the main activities of the first edition of the Advertising and Heritage Interpretation Summer School, which brought together students, young graduates, and professors from five faculties of Transilvania University of Brașov, four other Romanian universities, and five foreign universities: Meisei University Tokyo, Università Politecnica delle Marche, Università di Macerata, University of Zadar, and Salzburg University of Applied Sciences.
Keywords: heritage interpretation; advertising; marketing communication; project-based learning; international projects